The supplementation effect of Red Dragon fruit’s skin extract on the fasting blood glucose and lipid profiles in male Wistar rats with diabetes mellitus and dyslipidemia - Stefani Marietta; AAG Budhiarta; I Wayan Weta (Indoscholar, 2020)
Background: Flavonoids, saponins, tannins, phenols, and vitamin-C contained in the Red Dragon fruit’s skin have a positive impact on glycemic control and lipid oxidation. This study aimed to determine the effect of Red Dragon fruit’s skin extract on reducing the fasting blood glucose (FBG) and improving the lipid profile of Wistar rats with diabetes and dyslipidemia. Methods: A randomized pre-test post-test control group experimental study was done on 22 male Wistar rats, aged 2-3 months that suffered from diabetes and dyslipidemia. Subjects were divided into the control group (given 2cc distilled water + 9 mg metformin) and the treatment group (given 160 mg red dragon fruit’s skin extract + 9 mg metformin) for 14 days. FBG and lipid profile measurements were done before and after the treatment. Data were analyzed using the compare mean test. Results: There was no significant mean difference of GDP between groups before (p=0.414) and after treatment (p=0.125), total cholesterol between groups before (p = 0.572) and after treatment (p=0.361), triglycerides between groups before (p=0.073) and after treatment (p=0.111). There was a significant mean difference of HDL between groups before (p=0.003) and after treatment (p=0.047), LDL between groups before (p=0.006) and after treatment (p=0.043). Although there were significant mean differences in HDL and LDL between groups before and after treatment, the pre-post treatment of HDL and LDL mean differences showed no significant mean difference (p=0.328 and p=0.704 consecutively). Conclusion: Red Dragon fruit’s skin extract treatment did not significantly reduce the mean FBG and lipid profile levels.